2008
DOI: 10.1155/2008/378574
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Referral of Soft Tissue Sarcomas

Abstract: Introduction and aims. It is well established that soft tissue sarcomas (STSs) are more effectively treated in a specialist centre. However, delays in time taken for a patient to be referred to a specialist centre may lead to a poorer prognosis. This study aims to identify the length of these delays and where they occur. Patients and methods. Patients with a proven STS were included. They were recruited from both outpatient clinics and from the surgical ward of the Royal Orthopaedic Hospital (Birmingham, UK). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 10 publications
1
43
0
2
Order By: Relevance
“…The reasons for this are not clear but a previous study suggests delays at every level of referral from initial symptoms to sarcoma centre, part of this delay being due to patient factors, part being due to general practitioners (GPs) and part at referring hospitals. 19 This study also showed that obesity did not correlate with larger size at diagnosis.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The reasons for this are not clear but a previous study suggests delays at every level of referral from initial symptoms to sarcoma centre, part of this delay being due to patient factors, part being due to general practitioners (GPs) and part at referring hospitals. 19 This study also showed that obesity did not correlate with larger size at diagnosis.…”
mentioning
confidence: 54%
“…In this study we have made no attempt to differentiate between causes of the long duration of symptoms in some patients or to investigate patient or doctor delay prior to diagnosis as this has been done previously. 19 It is possible that the slight increase in symptom duration for patients with bone tumours is due to a change in reporting behaviours by patients, be it exaggerating symptom duration now or underestimating in the past. A limitation of using symptom duration as a measure of changing medical practice is that it is subjective and vulnerable to significant recall bias, an effect that is amplified as length of history increases.…”
Section: Discussionmentioning
confidence: 99%
“…17 It is well-recognised, however, that soft tissue sarcomas present late with the average size of presentation of a deep extremity sarcoma being 8 cm and that of a superficial sarcoma being 3 cm. 5,18 The reason for late presentation is not entirely understood but is partly because many of these sarcomas will have no symptoms other than the presence of a painless mass. Many sarcomas, especially those associated with a poor prognosis, arise in deep-seated anatomical locations such as the retroperitoneum or proximal extremity muscle groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some good reasons are shown in this study. Delay of referral is significantly higher (p < 0.001) in patients not initially treated at tertiary referral centres leaving patients in the dark about their diagnosis and further treatment options [8,10]. The need for wide resection of potentially contaminated tissue in re-operations leads to larger and more mutilating surgery with a higher need for reconstructive plastic surgery (p ¼ 0.009) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore current guidelines for patients presenting with a soft tissue mass either 5 cm in size and, or underneath the superficial investing fascia and, or painful and, or increasing in size recommend referral to a tumour centre [4,5]. Despite these guidelines the rate of inadequate surgical treatment prior to referral ranges between 30 and 60% and according to literature almost every physician treating patients with STS is confronted with this problem [2,[6][7][8][9][10][11][12][13][14]. It seems to be proven by numerous retrospective studies that re-excision of the residual tumour and=or the surgically contaminated area with the aim of wide resection margins leads to similar survival rates, similar recurrence rates and similar incidence of metastases compared to results after initial surgery with wide resection margins [6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%